2004
DOI: 10.1071/zo04007
|View full text |Cite
|
Sign up to set email alerts
|

The helminth parasites of Melomys cervinipes (Rodentia : Muridae : Hydromyinae)

Abstract: Melomys cervinipes Gould is one of four melomys species native to Australia. There have been no systematic surveys of parasite distribution and prevalence, or parasite community structure, for any species of Melomys. We present a comprehensive summary of the parasites of M. cervinipes by location in Queensland and northern New South Wales from published records, examination of museum specimens and data from an intensive sampling of hosts from four localities within central Queensland. An updated list prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Angiostrongylus cantonensis is a parasite of the pulmonary arteries and right ventricle of numerous wild Rattus spp., Bandicota indica, Melomys burtoni , M. cervinipes and Suncus murinus in the Asian, Pacific and Australian regions ( Mackerras and Sandars, 1955; Cross, 1979a; Smales et al., 2004 ). Discovered originally in the pulmonary arteries and right ventricle of Rattus rattus and R. norvegicus in Guangzhou, China ( Chen, 1935 ), it spread subsequently to South Asia, the Pacific islands and Australia where it is endemic ( Alicata, 1988 ).…”
Section: Host and Geographic Distribution Of Species Occurring In Wilmentioning
confidence: 99%
“…Angiostrongylus cantonensis is a parasite of the pulmonary arteries and right ventricle of numerous wild Rattus spp., Bandicota indica, Melomys burtoni , M. cervinipes and Suncus murinus in the Asian, Pacific and Australian regions ( Mackerras and Sandars, 1955; Cross, 1979a; Smales et al., 2004 ). Discovered originally in the pulmonary arteries and right ventricle of Rattus rattus and R. norvegicus in Guangzhou, China ( Chen, 1935 ), it spread subsequently to South Asia, the Pacific islands and Australia where it is endemic ( Alicata, 1988 ).…”
Section: Host and Geographic Distribution Of Species Occurring In Wilmentioning
confidence: 99%
“…Orders. These include (complied from Johnston and Mawson 1941;Mackerras 1958;Sprent and Mines 1960;Mawson 1961;Sprent 1963;Sprent and McKeown 1967;Bhaibulaya 1968Bhaibulaya , 1979Freeland 1983;Beveridge 1985;Hugot and Quentin 1985;Spratt andSingleton 1986, 2001;Singleton et al 1991;Gibbons and Spratt 1995;Smales 1997Smales , 2009Smales et al 2004 and Trichurus muris) and unidentified microfilaria (Mackerras 1962). Freeland (1983) suggested that Ophidascaris robertsi does not readily infect M. cervinipes in the natural environment, although M. cervinipes does demonstrate susceptibility in a laboratory environment.…”
Section: Diseases and Parasites -Melomys Cervinipes Carries Several I...mentioning
confidence: 99%
“…23 Apart from birds, R. celebensis has been reported from Rattus colletti 24 and Melomys cervinipes. 25 Ants have been demonstrated as intermediate hosts for Raillietina spp. in the emu.…”
Section: Discussionmentioning
confidence: 99%